Development of a High‐Affinity Antibody‐Binding Peptide for Site‐Specific Modification. (25th March 2021) - Muguruma, Kyohei; Osawa, Rento; Fukuda, Akane; Ishikawa, Naoto; Fujita, Konomi; Taguchi, Akihiro; Takayama, Kentaro; Taniguchi, Atsuhiko; Ito, Yuji; Hayashi, Yoshio
Abstract: Immunoglobulin G (IgG)‐binding peptides such as 15‐IgBP are convenient tools for the site‐specific modification of antibodies and the preparation of homogeneous antibody–drug conjugates. A peptide such as 15‐IgBP can be selectively crosslinked to the fragment crystallizable region of human IgG in an affinity‐dependent manner via the ϵ‐amino group of Lys8. Previously, we found that the peptide 15‐Lys8Leu has a high affinity ( K d =8.19 nM) due to the presence of the γ‐dimethyl group in Leu8. The primary amino group required for the crosslinking to the antibodies has, however, been lost. Here, we report the design and synthesis of a novel unnatural amino acid, 4‐(2‐aminoethylcarbamoyl)leucine (Aecl), which possesses both the γ‐dimethyl fragment and a primary amino group. A peptide containing Aecl8 (15‐Lys8Aecl) was synthesized and showed a binding affinity ten times higher ( K d =24.3 nM) than that of 15‐IgBP ( K d =267 nM). Fluorescein isothiocyanate (FITC)‐labeled 15‐Lys8Aecl with an N ‐hydroxy succinimide ester at the side chain of Aecl8 (FITC‐15‐Lys8Aecl(OSu)) successfully labeled an antibody (trastuzumab, Herceptin ® ) with the fluorophore. This peptide scaffold has both strong binding affinity and crosslinking capability, and could be a useful tool for the selective chemical modification of antibodies with molecules of interest such as drugs. Abstract : Two in one : A novel unnatural amino acid 4‐(2‐aminoethylcarbamoyl)leucine (Aecl) was synthesized and used to develop a high‐affinity IgG‐binding peptide. Synthesized Aecl‐containing peptides not only showed their strong binding affinity but also efficiently labeled trastuzumab. This suggests that 15‐Lys8Aecl is a useful tool for the site‐specific modification of native antibodies, leading to the preparation of homogeneous antibody–drug conjugates.